2017
DOI: 10.1136/jramc-2016-000759
|View full text |Cite
|
Sign up to set email alerts
|

Do air-gaps behind soft body armour affect protection?

Abstract: This work suggested that an air-gap behind police body armour might result in an increased likelihood of injury. It is recommended that body armour is worn with no air-gap underneath.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…One of the main areas of concern with relation to armour design for females is the correct fit. Tilsley et al, demonstrated that a 10 mm airgap under the armour can increase the risk of a ballistic projectile perforating the armour when compared to an armour that is close fitting to the body (Tilsley et al, 2018). Air gaps can form above, between and below the breast depending on how the armour is designed which could potential result in a ballistic perforation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main areas of concern with relation to armour design for females is the correct fit. Tilsley et al, demonstrated that a 10 mm airgap under the armour can increase the risk of a ballistic projectile perforating the armour when compared to an armour that is close fitting to the body (Tilsley et al, 2018). Air gaps can form above, between and below the breast depending on how the armour is designed which could potential result in a ballistic perforation.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, body armour is designed to sit close to the body to aid the dissipation of energy during a ballistic impact. It has been shown in previous work, that even small air gaps of 10 mm can increase the probability of a round perforating the armour (Tilsley et al ., 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Hard armor often consists of composite or ceramic plates and is mainly used to protect the thorax and abdomen ( Breeze et al, 2016 ; Neves Monteiro et al, 2017 ). It can achieve high levels of protection, but can be heavy and cumbersome ( Tilsley et al, 2018 ). Soft armor typically consists of flexible fabric panels, commonly in knitted or woven form, made from synthetic aromatic polyamides (aramids) or high-performance polyethylene (HPPE).…”
Section: Introductionmentioning
confidence: 99%